The Intervention of the Anti-Extradition Bill Movement in the Norms of Citizenship in Hong Kong. (February 2023) - Tang, Gary
Following the post-material shift of post-industrial societies, an evolution in citizenship norms from dutiful citizenship to engaged citizenship has occurred. This paper examines how people's attitudes towards the Anti-Extradition Bill movement are related to these two citizenship norms. Using data collected from a population survey ( N = 817), this paper shows that the people supporting the movement and radicalism perceived dutiful citizenship to be less important and engaged citizenship to be more important. The compatibility between the two sets of citizenship was found to be stronger among the people who supported the movement, despite the frequent appearance of unlawful behaviour in the movement. To explain the moderating effect, observations from focus group interviews revealed that some people had a traumatic experience in the movement. This trauma led them to doubt the legitimacy of the authority. Therefore, although they perceived dutiful citizenship to be important, they could also support various unlawful behaviours that occurred in the movement.